Can Corporate Income Tax Cuts Stimulate Innovation?. (August 2020) - Atanassov, Julian; Liu, Xiaoding
Abstract : We hypothesize that corporate income taxes distort firms' incentives to innovate by reducing their pledgeable income. Using a differences-in-differences methodology, we document that large corporate income tax cuts boost corporate innovation. We find a similar but opposite effect for tax increases. Most of the change in innovation occurs 2 or more years after the tax change, and there's no effect before the tax change. Exploring the mechanisms, we show that tax cuts have a stronger impact on innovation for firms with weaker governance, greater financial constraints, fewer tangible assets, smaller patent stock, and a greater degree of tax avoidance.